2022
DOI: 10.1177/20592043221106478
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Social Experience of a Concert Scales (SECS): The Social Experience of a Live Western Art Music Concert Influences People's Overall Enjoyment of an Event but not Their Emotional Response to the Music

Abstract: Social experience is often considered to be a key motivating factor for engaging with leisure activities and attendance at music concerts is no exception. Despite this, until recently, there has been limited interest in measuring the collective or social experience of live concerts in a quantitative way. Therefore, we created and validated a new measure of the social experience of a concert. In a pilot study, 103 participants were recruited across two concert settings . An extensive list of 65 items was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…However, the finding that there was a relation between neighbors’ motion and connectedness to the audience is compelling evidence that this single item (“to what extent did you feel connected to the audience?”) may have actually captured the intended latent variable. Since the present concert experiment was conducted, a scale for measuring social connectedness at Western art music concerts has been developed and validated (O’Neill & Egermann, 2022). Future research should certainly employ this 17-item scale when possible, within time constraints; however, the scale was developed for post-concert use and not for repeated measurements during a concert.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the finding that there was a relation between neighbors’ motion and connectedness to the audience is compelling evidence that this single item (“to what extent did you feel connected to the audience?”) may have actually captured the intended latent variable. Since the present concert experiment was conducted, a scale for measuring social connectedness at Western art music concerts has been developed and validated (O’Neill & Egermann, 2022). Future research should certainly employ this 17-item scale when possible, within time constraints; however, the scale was developed for post-concert use and not for repeated measurements during a concert.…”
Section: Limitationsmentioning
confidence: 99%
“…Social connectedness is an important component of the experience of concerts because one of the defining features of concerts is their social nature. Recent work by O’Neill and Egermann (2022) aimed to understand the social experience of concerts better through the development of a scale that combines measures grounded in parasocial interaction and in-group bonding (Horton & Richard Wohl, 1956; Leach et al, 2008). They found that the social experience of concerts was related to concert enjoyment, but not the emotional experience (O’Neill & Egermann, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides studies of the effects of musical activities on health and well-being using real-life interventions (e.g., Habibi et al, 2022;Jensen & Bonde, 2018;Kreutz, 2015), live concerts and performances have become a source of major interest (McAdams, 2004;Reynolds, 2004;Wald-Fuhrmann et al, 2021). The empirical methods used in such settings range from self-reports, sometimes continuous (Broughton et al, 2019;Egermann et al, 2013;O'Neill & Egermann, 2022), peripheral-physiology data (Czepiel et al, 2021) and motion capture (Swarbrick et al, 2018), to mention but a few. This trend toward the use of naturalistic concert settings in experiments on music perception is part of a wider momentum in the field (e.g., Tervaniemi, 2023) illustrated by the installation of expensive performance or concert halls specialized for research such as the Livelab at McMaster University in Hamilton, Canada (https://livelab.mcmaster.ca) and the ArtLab at the Max Planck Institute for Empirical Aesthetics in Frankfurt, Germany (https://www.ae.mpg.de/artlab/information.…”
Section: Music Psychology Beyond the Laboratorymentioning
confidence: 99%
“…This question is motivated by prior results suggesting that physiological synchrony between participants reflects social aspects (Konvalinka et al, 2011), and is higher when participants are co-present (Golland et al, 2015). Indeed, concerts likely create a social experience (Dotov & Trainor, 2021;O'Neill & Egermann, 2022). Thus, the social presence of others might be reflected in similarity of self-reports and neural measures (Chabin et al, 2022;Golland et al, 2015).…”
Section: The Effect Of the Concert Contextmentioning
confidence: 99%